The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/pds.3495
|View full text |Cite
|
Sign up to set email alerts
|

Medications in the first trimester of pregnancy: most common exposures and critical gaps in understanding fetal risk

Abstract: Purpose To determine which medications are most commonly used by women in the first trimester of pregnancy and identify the critical gaps in information about fetal risk for those medications. Methods Self-reported first-trimester medication use was assessed among women delivering liveborn infants without birth defects and serving as control-mothers in two large case-control studies of major birth defects. The Teratology Information System (TERIS) expert Advisory Board ratings of quality and quantity of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
1
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 11 publications
6
143
1
17
Order By: Relevance
“…Similarly, Thorpe et al (2013) found in a case control study that analgesics are largely consumed by pregnant women and acetaminophen was the most used. The use of this medicine during pregnancy is not associated with increased risk of abortion, stillbirth, low weight birth or increased prevalence of congenital anomalies Rebordosa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Thorpe et al (2013) found in a case control study that analgesics are largely consumed by pregnant women and acetaminophen was the most used. The use of this medicine during pregnancy is not associated with increased risk of abortion, stillbirth, low weight birth or increased prevalence of congenital anomalies Rebordosa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in the first 10-12 weeks of gestation [100,101]. Known teratological agents include, for instance, certain medications or drug of abuse taken by the pregnant woman, exposure to X-rays and elevated temperature, secondary to infectious diseases [102].…”
Section: Fetal Susceptibility To External Insultsmentioning
confidence: 99%
“…They must decide what to eat, what to drink, what test they will undergo and nearly every pregnant woman faces a decision about whether or not to take a medication during pregnancy, ranging from over-the-counter (OTC) antacids for gastroesophageal reflux to prescription medications for life-threatening chronic conditions (2,3). In the last three decades the use of medications during pregnancy has increased and it is now common during pregnancy (3,4). Estimates of the usage prevalence of at least one prescription medication during pregnancy range from less than 30 % to over 90 % of women (3).…”
Section: Introductionmentioning
confidence: 99%
“…The safety of medication use during pregnancy is frequently unclear because, for the majority of medications, there is a lack of sufficient data available to fully characterise the foetal risk. Thus, it is difficult to make informed clinical decisions about the best management of acute and chronic disorders during pregnancy (3,4). Since 1979, health care providers used a standard five-letter nomenclature published by the Food and Drug Administration (FDA) to assign a pregnancy risk category to medications (6).…”
Section: Introductionmentioning
confidence: 99%